The Manifested Dimension of Concept - Patricia Moya C. (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The article develops the hypothesis that the way Thomas Aquinas understands conceptexpresses his characteristic understanding of man as a subject inserted in the world. The direction of human knowledge towards the world establishes an inevitable tension between the universality of theconcept (on the one hand) and the necessary application made by understanding (on the other) as without this application knowledge is not attained entirely. The insistence on the central character of «application» is made evident in the conversio ad phantasma doctrine. The concept expresses the perfection of the subject, his actualization as well as the intentionality of the operation. Both aspectsclaim each other, because the formal or representative possession of knowledge is at the same time remitted to matter. Knowledge is not therefore a derivation of the representation towards real things, but a non inferential transit towards them.